SOCIO-ECONOMIC EMPOWERMENT THROUGH ICT EDUCATION: A COMPARATIVE ANALYSIS OF MAHARASHTRA AND RAJASTHAN IN INDIA - Krishnan Narayanan (International Conference on the Convergence of Knowledge, Culture, Language and Information Technologies December 2 - 6, 2003, Alexandria, EGYPT, 2003)
Human development despite faltering economic development has been taking place in India, how much ever gradually, in many states. While the formal Government sector continues to play an important role, it is the growth of private participation in providing affordable computer education, especially to the socially and economically under-privileged that appear to have provided the impetus for growth in qualified professionals. This paper argues that education and training in computer programme and packages at subsidized rates is likely to increase the capabilities for job-seeking, which in turn would change the socio-economic structure of the households whose members have been the beneficiary of such programme. The results of this study, which compares two Indian states representing the economically prosperous and under-developed, points out that computer education appears to have tremendous scope to enhance poor people's opportunities, and be a major source of empowerment of people - especially the socially and economically backward - in India.